Etyka brokera ubezpieczeniowego - Wieteska, Stanisław (Annales. Etyka w Życiu Gospodarczym, 2008)
A broker’s activity is one of the elements of insurance mediation. Brokers sell property and personal as well as life insurance policies. Apart from the range of duties, the quantitative condition of distribution channels, the paper also discusses problems of a broker’s professional ethics, which include broadly understood information reliability, activation honesty and assistance in damage liquidation. Signed in 1998, the Sobieszew Charter lays out the norms of ethical broker’s activity in three dimensions: their contacts with clients, mutual contacts and contacts with an insurance company. As well as that, the Charter created the Commission of Professional Ethics, the role of which is settling conflicts arising in the above-mentioned dimensions. The Charter also established seven main principles of professional ethics including the principle of a fair turnover or that of forming healthy relationships among brokers. The paper investigates the data concerning ethics in broker organizations, the major elements of which are a broker’s impartiality, conducting honest negotiations and the duty of submitting identical requests for proposal to insurance companies. The issue of insurance brokerage is not discussed.